Recent advances in scaling-up of non-conventional extraction techniques: Learning from successes and failures - Belwal, Tarun; Chemat, Farid; Venskutonis, Petras Rimantas; Cravotto, Giancarlo; Jaiswal, Durgesh Kumar; Bhatt, Indra Dutt; Devkota, Hari Prasad; Luo, Zisheng (TrAC Trends in Analytical Chemistry, 2020)
The impact of the extraction technologies on product yield and analytical profile is relevant. This review is aiming to discuss recent experiences of successes and failures in non-conventional extraction scaling-up, to better understand the challenges and designing of existing and new techniques. Understanding the crucial extraction factors at laboratory and pilot scale is of paramount value for the engineering work of scaling-up. Besides, a careful analysis and modelling of heat and mass transfer and energy consumption, the design of industrial extraction plants driven by economic and environmental factors, are well covered in the present review. Current trend strongly favors scaling-up of green approaches that consumes less organic solvent(s), involves minimal operational steps, provides high throughput capability and assures highest yield at lower costs. Current and future challenges in scaling-up extraction of bioactive compounds require a parallel development of suitable analytical methods to monitor the process and ensure high yield and quality. •Recent advances in extraction scale-up studies with non-conventional techniques.•Enabling technologies and analytical monitoring in industrial green extraction.•Hybrid techniques and continuous processes for extraction industrialisation.•Extraction kinetics and modeling for extraction optimisation.•Technology readiness levels (TRLs) in green extraction scaling-up.